PENGARUH KUALITAS PELAYANAN DAN PERSEPSI RISIKO TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN JASA EKSPEDISI J&T EXPRESS SAMARINDA - Bangkit Bimantara (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
The purpose of this research is to find an independent variable consisting of service quality X1 and X2 ( risk perception ) influences the dependent variable customer satisfaction (Y).The population of the research is every consumer J&T that use the expedition was .The sample collection technique using simple random sampling .Included in this research using formulas slovin 100 respondents .The research is quantitative research .Data collection techniques that is by using data primary and secondary data .A scale of measurement data using likert scale .Use the instrument for testing the classic , the data analysis techniques in a linear regression multiple. The results of the study showed that of the study are variable risk perception is the variable against the customer satisfaction in the most influential in the use of services expedition J&T in Samarinda. Expedition J&T in samarinda should increase customer customers with the figure in a receptive manner opinion of consumers.